Biomassa e estoque de nutrientes em diferentes materiais genéticos de Eucalyptus no sul do Brasil - Santos, Kristiana Fiorentin dos (2018)
The study of biomass production and nutrient accumulation in Eucalyptus stands as the basis for understanding nutrient dynamics in forest sites. The objective of this work was to estimate the biomass and nutrient stock of different genetic materials of Eucalyptus in two regions of the state of Rio Grande do Sul, Brazil. The research was conducted in experimental areas located in São Gabriel and Eldorado do Sul, in 43- and 49-month-old stands, respectively. In the sites, the following Eucalyptus clones were implanted: E. benthamii (P1), E. benthamii (P2), E. saligna, E. dunnii, E. uroglobulus, and E. urograndis. In each region, above-ground biomass sampling was performed from three medium trees, for each genetic material. The selected trees were fractionated into leaves, branches, stembark, and stemwood. Subsequently, a representative sample of each fraction was collected for analysis of the macro- and micronutrients. The coefficient of biological utilization was calculated by the ratio between the biomass and the amount of nutrients in each biomass component. The estimated biomass export of nutrients was calculated for three scenarios. In São Gabriel, the biomass ranged from 33.68 to 84.00 Mg ha-1, with E. uroglobulus having the highest production and E. dunnii the lowest. The tree canopy accumulated between 47 % and 65 % of the total macronutrients and 46 % to 67 % of the total micronutrients (E. benthamii (P2) and E. urograndis), while the stem accounted for 35 % to 53 % of the total macronutrients and 33 % to 54 % of the total micronutrients. For the stemwood, E. saligna was found to have the best efficiency of use for N, P, K, S, and Mn, and E. uroglobulus for Mg, B, and Zn. The highest amounts of nutrients exported with biomass harvesting, for the first and second scenario (stemwood harvesting and stemwood with bark harvesting), occurred in E. uroglobulus (N, K and S), E. urograndis (P, Mg and Cu) and E. saligna (Fe, Zn and B). For the third scenario (stem and canopy), the highest nutrient exportation occurred in E. urograndis, except for S, where the highest removal occurred in E. uroglobulus. In Eldorado do Sul, biomass production ranged from 68.40 to 117.52 Mg ha-1, with the highest levels in E. dunnii and E. uroglobulus, with lower and higher total biomass production. The tree canopy accumulated between 17 % and 52 % of the total macronutrients (E. benthamii (P1) and E. uroglobulus) and from 24 % to 34 % of the total micronutrients (E. dunnii and E. uroglobulus). While the stem accumulated between 48 % to 83 % and 66 % to 76 % of the total macro and micronutrients, respectively. For the stemwood, it was observed that E. benthamii (P2) presented the highest values of nutritional efficiency for N, Ca, Cu, and Fe, and E. globulus for P, Mg, and B. In relation to the estimation of nutrient exports, in the first scenario (stemwood harvesting) the highest amounts of nutrients exported with the biomass harvest occurred in E. uroglobulus (N, K, S, and Fe) and E. urograndis (Ca, B, Cu, and Zn). For the second scenario (stemwood with bark harvesting), the highest amounts of nutrients removed occurred in E. uroglobulus (N, K, S, and Fe) and E. benthamii (P2) (P, Ca, B, and Mn). Additionally, in the third scenario (stem and tree canopy) the highest nutrient exportation occurred for E. benthamii (P1) (P, Ca, B, Mn and Zn), E. uroglobulus (N, K, S, and Fe) and E. grandis (Mg and Cu). In both regions, variations in concentrations and amounts of nutrients between the genetic materials and their different components were observed. In general, the highest coefficient of biological utilization values were found in the wood, and the lowest in the leaves. Although the site of São Gabriel showed a higher fertility, there was less biomass production in this area; this could be attributed to less favorable soil physical characteristics. In Eldorado do Sul, where soil fertility is lower, the nutrient utilization efficiencies of some species stand out compared to that of species in São Gabriel. Regardless of the site and genetic material, harvesting only the wood of the trunk showed the least removal of nutrients from the system.